2022
DOI: 10.1039/d1nh00626f
|View full text |Cite
|
Sign up to set email alerts
|

Hitchhiking probiotic vectors to deliver ultra-small hafnia nanoparticles for ‘Color’ gastrointestinal tract photon counting X-ray imaging

Abstract: Gastrointestinal (GI) tract is one of the hard-to-reach target tissues for the delivery of the contrast agents and drugs mediated by the nanoparticles due to its harsh environment. Herein, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…To some extent this is related to the biological relevance of iron oxide and its incompatibility with NMR spectroscopy. However, hafnium oxide is also a valuable nanocrystal for biomedicine, and it is compatible with NMR. This is currently the focus in our own research group.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent this is related to the biological relevance of iron oxide and its incompatibility with NMR spectroscopy. However, hafnium oxide is also a valuable nanocrystal for biomedicine, and it is compatible with NMR. This is currently the focus in our own research group.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,70,103,122,123 Spherical hafnia nanoparticles with diameters below 100 nm are most commonly studied for medical applications. [5][6][7][8]21,76 Other reported morphologies for hafnium-based therapeutic agents include mesoporous spherical structures (130 nm), 38 rods (40 × 100 nm), 87 and ellipsoids (40−400 nm). 124 Sahraneshin et al 29 demonstrated the influence of reaction temperature on shape during hydrothermal synthesis and prepared trapezohedron (16 nm) and oval (16 nm) shaped hafnia particles.…”
Section: Characterization and Morphologymentioning
confidence: 99%
“…Stringent histopathology studies illustrated a high level of safety and lack of toxicity from the particles. In a separate published work, 7 this group prepared a hafnia-based contrast agent targeted for the gastrointestinal tract. Targeting was accomplished via microencapsulation of ultrasmall hafnia particles within a probiotic system.…”
Section: Applications In Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hafnium oxide exhibits strong contrast enhancement in conventional radiography and CT due to its high density, favorable K-edge, and the high atomic number of the metal . HfO 2 nanocrystals are biocompatible ,, and have already seen clinical use as a radiotherapy enhancer. , As a diagnostic contrast agent, cationic HfO 2 nanocrystals exposed bone-microdamage in vivo , and using probiotic vectors HfO 2 nanocrystals allowed imaging the gastrointestinal tract . While multimodal imaging probes for other oxides such as iron oxide nanoparticles have been developed, none are currently available for HfO 2 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%